The Resolution of Disputes in the Village Head Election of Kuripan, East OKU, 2023 - Sephia, Sephia (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
The Village Head Election is a contest for power at the village level. During this election process, conflicts can sometimes arise between supporters and the candidates for the village head position. One intriguing case in Indonesia regarding conflicts in village head elections is the 2023 Village Head Election in Kuripan, located in the Kuripan District, East OKU Regency. In this election, the candidate with number one won by a margin of only one vote over the candidate with number two, accompanied by several indications of irregularities in the election process. This research employs a descriptive qualitative method with data collection techniques including interviews and documentation. Primary data sources include interviews, while secondary data sources include literature. The findings of this study reveal that the dispute in the Kuripan village head election in the Cempaka District, East OKU Regency, was resolved through a local mechanism resembling a village deliberation, or other similar terms referring to discussions involving all relevant village stakeholders. These include the election committee, village government officials, and village representative bodies. To prevent disputes in future village head elections, it is recommended to clarify and improve the transparency of the election information and process.